Kamuflase Politik Dalam Alat Peraga Kampanye - Pinem, Kamarlin (JUPIIS: Jurnal Pendidikan Ilmu-ilmu Sosial, 2014)
Billboards, banners, posters, flags, photographs, and the other campaign medias in various sizes, were crowded the private and public spaces of the city.Â  As if, what were displayed in our daily was the truly images of the candidates of leader and public officials, and does not seems concerned with the aesthetics of the city and public opinion. The aesthetics of spatial order of the city became chaotic due to almost all of political parties did not concern the regulation of General Election Commission No. 15 of 2003. As a regu-lation which was enacted for regulating of displaying campaign medias which are potentially chaotic, and to maintain the order and aesthetics of the city. The campaign medias were not placed on praying homes, hospitals, or the places of health services, government office buildings, educational buildings, higway, infrastructure and public facilities, and city parks (Article 17 General Election Com-mission regulation No 15 of 2013)